2018
DOI: 10.1167/iovs.18-25515
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Analysis of Weighted Genes in Diabetic Retinopathy

Abstract: PURPOSE. Intricate signaling networks and transcriptional regulators translate pathogen recognition into defense responses. The aim of this study was to identify the weighted genes involved in diabetic retinopathy (DR) in different rodent models of diabetes. METHODS. We performed a gene coexpression analysis of publicly available microarray data, namely, the GSE19122 dataset from the Gene Expression Omnibus database. We conducted gene coexpression analysis on the microarray data to identify modules of function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…With the rapid development of next-generation sequencing technology and bioinformatics, more and more non-coding RNAs (ncRNAs) are identified to be involved in the human multiple diseases. 17,18 LncRNA PVT1 has been reported as a diabetes-related ncRNA transcript. [19][20][21] In this research, we found that the lncRNA PVT1 was remarkedly up-regulated in the diabetic cataract (DC) tissue and high glucose (HG)-administrated HLE B-3 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the rapid development of next-generation sequencing technology and bioinformatics, more and more non-coding RNAs (ncRNAs) are identified to be involved in the human multiple diseases. 17,18 LncRNA PVT1 has been reported as a diabetes-related ncRNA transcript. [19][20][21] In this research, we found that the lncRNA PVT1 was remarkedly up-regulated in the diabetic cataract (DC) tissue and high glucose (HG)-administrated HLE B-3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid development of next‐generation sequencing technology and bioinformatics, more and more non‐coding RNAs (ncRNAs) are identified to be involved in the human multiple diseases . LncRNA PVT1 has been reported as a diabetes‐related ncRNA transcript .…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatic analysis is a well-established method that is widely used to help researchers identify potential biomarkers. 27 Thus, we performed bioinformatic analysis of the GEO database to reveal that TRIM59 was one of the most upregulated genes in retinoblastoma samples, which was consistent among the three datasets analyzed. Through qRT-PCR and immunoblotting, we verified that the level of TRIM59 in retinoblastoma cells differed significantly from that in control cells.…”
Section: Discussionmentioning
confidence: 76%
“…It is well known that the initiation and progression of diabetesinduced multisystem complications are complex pathological processes associated with inflammation (23,30,43,59). Pyroptosis is a novel type of programmed cell death related to the activation of inflammation (4).…”
Section: Introductionmentioning
confidence: 99%